USE OF PRUNES AS A CONTROL OF HYPERTENSION - Ahmed, Talat; Sadia, Halima; Batool, Sadia; Janjua, Ayesha; Shuja, Faiza (Journal of Ayub Medical College Abbottabad, 2010)
Background: Fruits and vegetables are shown to reduce blood pressure. It is not merely the antioxidants contained in fruits and vegetables that have health benefits such as lowered systolic and diastolic blood pressures. This study was undertaken to see the cardiovascular protective effects of prunes. Methods: A placebo controlled clinical trial study was designed to see the effects of Prunus domestica on blood pressure in 259 pre-hypertensive (Systolic BP=120-139 mmHg, diastolic BP=80-89 mmHg) volunteers. Treated groups drank prune juice and ate the whole fruit (dried plums) while either 3 (about 11.5 gm) or 6 prunes were soaked overnight in a glass of water whereas control group took only a glass of plain water early in the morning on empty stomach. Blood pressure was recorded fortnightly for 8 weeks, and blood samples were taken at 0 and 8 weeks. Results: There was significant reduction of blood pressure by single dose of prunes daily group and the controls (p<0.05). With the double dose of prunes, only systolic BP was reduced significantly (p<0.05). Control group had significantly increased serum HDL whereas test groups had significantly reduced serum cholesterol and LDL (p<0.05). Data was analysed by paired-sample t-test with 95% confidence interval. Conclusion: The data predicts cardiovascular protective effects of prunes. Keywords: Plums, Prunus domestica, blood pressure, lipid profile, pre-hypertensive patients